Health trauma and well-being assistant for Bengali seniors in household: a multimodal approach - Islam, Md. Nazmul; Al-Amin, Md.; Hassan, Md. Zaed; Islam, Tamzid (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.